# algebra

posted by .

can someone tell me if i did the problem correct (solve by completing the square) 4x^2+2x-3=0
x^2+(1/2)=3/4
x^2+(1/2)+(1/4)^2=3/4+(1/4)^2
(x+1/4)^2=13/16
x+1/4=+-sqrt 13/16
x+1/4=+-sqrt 13/4
x=-1/4+-sqrt 13/4
x=-1+-sqrt 13/4

• algebra -

x^2+(1/2)=3/4 should say

x^2+(1/2x)=3/4 also in the line that follows that you left out the x in the second term

to avoid problems with order of operation, write your final answer this way

x=(-1+-sqrt 13)/4 the way you have it only the square root term would be divided by 4

## Similar Questions

l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
2. ### Inequality

When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?

4. ### math,algebra,help

Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
5. ### Math

How do you find a square root of a number that's not a perfect square?
6. ### math,help,algebra I

I need help can someone help me get unstuck and let me know if i am correct.thank you. solve by completing the square. 4x^2+2x-3=0 this is what i am doing: i used the quadratic equation. so where i am is in this step: x = (-2 (+-) …